PREDIKSI EROSI LAHAN PADA DAS AIR DINGIN BAGIAN HULU DI KOTA PADANG (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2017)
This research was conducted to identify the land in Watershed Air Dingin In Part Upstream Padang City based on the level of erosion and conservation directives. The method used to determine the level of erosion is determined based on a formula USLE (Universal Soil Loss Equation) and conservation directives refers to the modification of Kumajas (1992). The results showed very mild erosion is 5.93 tonnes/ha/year with an area of 58.61 ha, mild erosion is 43.9 tonnes/ha/year with an area of 24.49 ha, ie erosion was 181.64 tons/ha/year with an area of 3.91 ha and severe erosion which 74.91 tonnes/ha/year with broad 4.33 ha.Whereas conservation direction on very mild erosion on slopes IV (≥ 40 %) were left in a natural state, mild erosion on slopes III (26 – 40 %) is performed with a bench terracing, erosion was on the slope II (14 – 25 %) do with crop rotation with a terrace by the width (mulsa utilization) and the weight carried by erosion bench terraces (Cultivation with human labor).